Proposed new interior design scheme of ‘Butik Tekat Senang Emas' for Gesamas Sdn Bhd at Lot 4307N -4312N, Jalan Leong Sin Nam, Bandaraya Ipoh, Perak Darul Ridzuan / Robiatul Adawiah Shamsudin - Shamsudin, Robiatul Adawiah (Faculty of Architecture, Planning and Surveying, 2011)
The final project for student of Diploma Interior Design is a manisfestation towards the student’s knowledge about the whole aspect on interior design that had been learned from basic until the final presentations on the proposed design. The project that had been chosen for the final project is proposed new interior design of ‘Butik Tekat Benang Emas Perak’ for Gesamas Sendirian Berhad at Lot 4307N - 4312N, Jalan Leong Sin Nam, Bandaraya Ipoh, Perak Darul Ridzuan . This proposed boutique gallery is to attract users, nation’s youth and especially on tourist to experience Malaysian identity and culture, at the same time to promote Malaysian unique craft product. The target market for the customer of this kraftangan product is tourist from all over the world that are curious about Malaysian heritage. This also preserving the art of our fathers not to swallow the time lapse. Concept and images that had been chosen not only must be suitable with the client’s as both of it would reflect the client itself, but at the same time it would give a positive impact to the people. The concept had been chosen in this proposed is ‘Preserving The Perak Legacy’. The meaning from the tagline is connected about the heritage of this kraftangan. Its about the glory heritage uniqueness of Malaysian culture.